Penggunaan Aplikasi Tiktok Shop Dalam Belanja Online Santri Nurul Ichsan Bontang - Muh. Ihsan; Rosadi, Khumaini (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2023)
Nowadays, when you want to go shopping, you don't have to bother going out of the house. It is enough to have a gadget and download the TikTok application, so you can search for the current products you are looking for. Only by swiping the gadget screen, if you are interested in the image catalog displayed, then click shopping. Payment can be transferred directly or paid on the spot. At Nurul Ichsan Islamic Boarding School every day there are couriers delivering packages to the students. Some use the COD payment method or pay on the spot, some have paid directly via transfer, and some have paid in installments. The items purchased by the students also varied. Starting from learning equipment such as mushafs of the Koran, clothes such as robes and modern clothes, cosmetics and beauty tools such as skincare, to even buying lato-lato viral games through the TikTok shop. even the couriers are very familiar with the students who often shop online because every day there are shipments of goods to Islamic boarding schools, both male students and female students. So, from the large number of students who shop online and the frequent couriers coming to deliver packages to Islamic boarding schools, I wrote this research so that it becomes a lesson and education for students, so they don't become consumptive or wasteful in spending things that are not needed. With this research, it is an appeal to students so that what is spent is in accordance with what is needed, not just desires, following the trend that is currently viral, so that the money does not run out in vain. Not redundant, because redundant is a friend of satan. Santri are expected to be able to dampen their passions so they are not affected by the temptations of online shopping.